2000
DOI: 10.1300/j077v18n04_02
|View full text |Cite
|
Sign up to set email alerts
|

Interest in a Support Group Among Individuals Tested for a BRCA1 Gene Mutation

Abstract: This article explores interest in a support group among 218 individuals tested for a mutation in BRCA1, a breast and ovarian cancer susceptibility gene. When queried 4 to 7 months after receiving the BRCA1 test results, approximately one-fourth of the participants expressed interest in a hypothetical support group. A mixed-carrier status and multiple family group was preferred over a carrier-only and single-Ms. Hamann is a Doctoral Student,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Support groups are created as individuals seek out others who are similar to them in order to understand social reality (McGovern et al, 2002). These groups can provide an environment and a forum where individuals can have access to medical information, psychologi-cal information and education, and emotional support (Hamann et al, 2000). Mutual feelings and commonalties about long-term effects of HCT can be shared in a support group.…”
Section: Support Groupsmentioning
confidence: 99%
“…Support groups are created as individuals seek out others who are similar to them in order to understand social reality (McGovern et al, 2002). These groups can provide an environment and a forum where individuals can have access to medical information, psychologi-cal information and education, and emotional support (Hamann et al, 2000). Mutual feelings and commonalties about long-term effects of HCT can be shared in a support group.…”
Section: Support Groupsmentioning
confidence: 99%
“…Later, Pascoe, Edelman, and Kidman (2000) found that only 16% of a sample of oncology outpatients had attended a support group. Even among women who had undergone genetic testing for the BCRA1 mutation, only one-fourth expressed interest in attending a hypothetical support group (Hamann et al, 2000).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Contradictory findings appeared concerning social support: some studies found that those who participated in support groups experienced less social support in their social environment than nonparticipants [8-10], while others found no differences [6,11,12]. In general, participants seemed to be more anxious about their illness and had greater emotional problems than did nonparticipants [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…Such group participation can offer emotional support, confidence, and strength [ 1 ]; can foster hope [ 2 ]; and can lead to improved coping [ 3 ], less distress [ 4 ], and an improved quality of life for the participant [ 5 ]. Despite these empowering outcomes of engagement in peer support, studies have shown that many face-to-face peer support groups have only small numbers of participants [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation